Searchable Symmetric Encryption for Private Data Protection in Cloud Environments - Silveira, Matheus M.; Silva, Danielle S.; Rodriguez, Sandra J. R.; Gomes, Rafael L. (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2022: Companion Proceedings of the 11th Latin-American Symposium on Dependable Computing, 2022)
Cloud computing arose as a suitable environment to store data with reliable and scalable remote access, but it also represents new challenges regarding data protection and privacy issues. A suitable approach to overcome these challenges is the usage of encryption, which provides the protection and privacy aspects of data. However, in general, encrypted data can not be used by the original systems, since usual functions, such as database queries and computations, need the original data. Additionally, it is very expensive to perform encryption and decryption of the database to search and get data, since these techniques have a high computational cost. In order to deal with this scenario, this paper presents a tool to protect private data in databases of cloud environments using a new approach of Searchable Symmetric Encryption (SSE), preventing problems of data leakage and privacy breaches, while enabling users to store data maintaining the functionality to search keywords in their encrypted database. Our new approach of SSE overcomes slow processing limitation, enabling a higher effectiveness when considering huge databases and dynamical data. Results from real experiments using cloud environments suggest that the proposed solution is suitable to perform the encryption.